Batak Traditional Houses as a Source of Ideas in the Creation of Written Batik - Armojo, Wahyu Tri; Misgiya (Talenta Publisher, 2024)
The source of the ideas underlying this research is the uniqueness and uniqueness of the traditional house ornaments of the Toba Batak, Malay, Karo, Simalungun, Pakpak, Mandailing, and Nias traditional houses. The interest that emanated from the form of traditional house ornaments gave rise to motivation and inspiration to explore, design, and create in the form of creative batik motifs in North Sumatra. Engineering the aesthetic elements of traditional Batak Toba, Malay, Karo, Simalungun, Pakpak, Mandailing and Nias traditional houses as a real business using a development research scheme. The creation process goes through three stages, namely exploration, design, and embodiment. The batik technique uses written batik on mori cotton cloth and coloring with the dab technique. The work is in the form of batik clothing. Batik clothing with the Pakpak Dairi traditional house applies this type of motifconical inflorescence,perkupkup manun,siwaluh villageAndconical inflorescencewith the results of quality tests for modification of motifs, development of motifs, characteristics of motifs, neatness of cantings, coloring, and work models obtaining an average score of 90. Karo ornament batik applies the type of traditional house motif siwaluh jabu,mangosteen pantil,close the dice, Andcimba lau, with the results of quality tests of motif modification, motif development, motif characteristics, print neatness, coloring, and work models obtaining an average value of 90.22. Simalungun ornament batik has a traditional house motifstupid,hail putor,hair uow,Andpatundal thighswith the results of quality tests of motif modification, motif development, motif characteristics, print neatness, coloring, and work models obtaining an average value of 88.91. Toba Batak ornament batik has vizbolon house,simataniari,simeol-eolAndipon-iponwith the results of quality tests of motif modification, motif development, motif characteristics, print neatness, coloring, and work models obtaining an average value of 90.27. Mandailing ornament batik applies a type of motifgoddamn goodin jungleagodangmandailing,Burangir, Bindu, Gimbangand lotus flowers with the results of quality tests on motif modification, motif development, motif characteristics, inscription neatness, coloring, and work model obtaining an average score of 89.88. Nias ornamental batik has motifs such as:omg hada,niotalinga woli-woli,niotalakhoi(niotawolo),niohuluyo, niogama and niosolafigawith the results of quality tests of motif modification, motif development, motif characteristics, print neatness, coloring, and work models obtaining an average value of 89.38.